CBS News/60 Minutes/Vanity Fair National Poll, April #2, 2011 ([Verlag nicht ermittelbar], 2012)
This poll, fielded April 28 - May 1, 2011, is a part of a continuing series of monthly surveys that solicits public opinion on the presidency and on a range of other political and social issues. Respondents were asked for their opinions of political figures President Barack Obama, First Lady Michelle Obama, Tim Pawlenty, Sarah Palin, Donald Trump, Oprah Winfrey, and members of the royal family, Prince Charles and Lady Camilla. Opinions were sought on a range of topics that included abortion, the expected length of time United States troops will remain in Afghanistan, plans for the Memorial Day holiday, the economic dichotomy within the United States, and the quality of blockbuster movies today compared to ten years ago. Respondents were also asked whether detainees from Guantanamo Bay, Cuba could be held safely in United States maximum security prisons. Several questions sought the respondent's opinions on positive thinking, motherhood, happiness, and comparative consumption of home décor and furniture goods. A significant portion of the survey focused on the rising cost of gasoline. Respondents were asked their opinion of the future cost of gasoline, whether they've taken any specific steps to deal with the higher price of gasoline, whether they've suffered financial hardship due to the increased prices of gasoline, and whether they plan to change summer vacation plans. Additional topics included the Tea Party movement, reasons for the American Civil War, United States government participation in prosecuting professional athletes for cheating, legitimacy of graffiti as art, and lying about one's age. Demographic variables include sex, age, race, marital status, education level, household income, religious preference, political party affiliation, political philosophy, voter registration status, and whether respondents thought of themselves as born-again Christians.